You've got this : the life-changing power of trusting yourself - Warrell, Margie (Gildan Audio, 2020)
Does fear hold you back' We all have moments when we succumb to doubt and let our fears call the shots. Each time they do, we limit our lives. It's why learning to trust in ourselves is crucial to rising above our biggest challenges and enjoying true happiness and success-in our careers, relationships, leadership, and life. Written with heart and humor but grounded in research, You've Got This! is a handbook for unleashing our untapped potential and passion, creativity and courage, to thrive in today's uncertain world. Filled with compelling stories and hard-won wisdom, author Margie Warrell draws on her background in business, coaching, and doctoral studies, as well as her challenges raising four children while living and working around the world. Applying the practical advice and twelve powerful principles in this book will help you: defy negative self-talk and take the bold actions you've been putting off; become your greatest cheerleader, not your loudest critic; embrace vulnerability and trust your intuition; combat stress and thrive amid uncertainty; and amplify your power as a leader and "change maker."Hailed as a "high five to the human spirit," You've Got This! is a must-listen for everyone, from seasoned leaders, to those embarking on their adult lives, and anyone in between who just needs encouragement to take that leap.